Morphological and ecological characteristics of diatom species Stauroneis neofossilis Lange-Bertalot & Metzeltin 1996 (Bacillariophyceae) from Bosnia and Herzegovina (Annals of the Institute of Biology, 2022)
In mine pit lake Bistrik, which is located near Kakanj Municipality, a diatom species from the genus Stauroneis has been recorded and identified. In addition to the analysis of the composition of cyanobacteria and algae, the basic physical and chemical parameters of water were also measured. By comparing the morphometric characteristics of the valve of Stauroneis neofossilis, a similarity with the literature data was determined. The paper also presents LM and SEM micrographs of S. neofossilis and a list of identified species of the genus Stauroneis in Bosnia and Herzegovina. To obtain a more complete picture of morphometric characteristics, distribution and ecology, a detailed investigation of this genus from freshwater habitats in Bosnia and Herzegovina is necessary.